Russian women's national floorball team in regular season: postural control rating study - Gudkov, A. B.; Demin, A. V.; Dolgoborodova, A. A.; Bykov, A. V. (Theory and Practice of Physical Culture, 2017)
Abstract: Modern top-ranking international competitions are known to be of highest demand to every aspect of the athletic functional fitness in team sports. The article gives first accounts of the postural control profiling data - including the postural equilibrium and sensory functionality data - for players of the Russian Women`s National Floorball Team in the regular season. Computerized stabilometric/ posturagraphic method was used to find that the female floorball players having 5-years-minus international competitive experience tend to develop - as a result of the sport-specific physical, mental and emotional stresses - some deficiencies in the quality and adaptive capability of the postural equilibrium control; static neurophysiological mechanisms of postural control; and the vestibular and visual components of the postural equilibrium control in different game situations - as compared to the female floorball players having 5-years-plus international competitive experience. These postural control deficiencies of the female floorball players having 5-years-minus international competitive experience may be of negative effects on their competitive performance efficiency and success rates and increase their sport-specific injury risks.